Narcissitic Personality Disorder Pada Tokoh Elena Dalam Komik Tomodachi Gokko Karya Momochi Reiko - Wardhani, Komang Triyas; Damayanti, Silvia; Anggraeny, Renny (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2020)
The tittle of this research “Narcissitic Personality Disorder at Character Elena Figure in comic Tomodachi Gokko by Momochi Reiko”. The aims of this research are to described NPD Characteristic, the reasons of NPD in character Elena, impact of NPD to Elena and other characters in comic Tomodachi Gokko by Momochi Reiko.The theories that have been used are Wellek and Warren’s literature and psychology theory (2016), Sigmund Freud Narcissism theory (1914), Gunderson’s Narcissitic Personality Disorder (1994), Lajos Egri’s Three Dimensions of Characterrization (1946) and Marcel Danesi’s  semiotic theory (2011). Based on the result, Elena is an early adulthood’s girl who experiences with Narcissistic Personality Disorder. Characteristic of NPD in Elena based on Gunderson , dkk, namely (1) has a grandiose of self-importance and is often envious of others, (2)is preoccupied with fantasies of unlimited success, power, brilliance, beauty, or ideal love. (3) believes that he or she is “special” and unique and can only be understood by, or should associate with, other special or high status people, (4) requires excessive admiration, (5) has a sense of entitlement, (6) is interpersonally exploitative, takes advantage of other to achieve his or her own ends, (7) lacks empathy, and (8) shows arrogant, haughty behaviors or attitudes. The Reason behind Elena’s NPD condition was triggered by her mother, as a child she was often got curse word. The impact of  NPD to Elena were 1) difficulted for her to distinguish between good and bad deeds and she almost lost her own life, and she move to the new school. The impact Elena’s NPD to other people around her were 2) she doing bullying, damaging, and traping for personal gain. Keywords : psychology literature, Narcissistic Personality Disorders, Psychoanalytic